Phosphorus effects on biomass accumulation and nutrient uptake and removal in two potato cultivars - Soratto, Rogério P. [UNESP]; Fernandes, Adalton M. [UNESP] (Wiley, 2016)
Information on the effect of P fertilization on nutrient uptake and removal by potato (Solanum tuberosum L.) cultivars is required for proper soil nutrient management. This study was performed to evaluate how dry matter (DM) accumulation and partitioning, the uptake of nutrients, and their allocation to the tubers and removal in potato cultivars (Agata and Mondial) are affected by the P fertilization rates (0, 125, 250, 500, and 1000 kg ha−1 P2O5) placed in the furrow at planting as triple superphosphate. An experiment was conducted over 2 site-years in loam clayey Oxisols with low P availability in Sao Paulo State, southeastern Brazil. Both cultivars exhibited very similar DM accumulation, tuber yield, and nutrient uptake and allocation to the tubers when P was not supplied at planting. Phosphorus fertilization greatly increased the DM accumulation and nutrient uptake and removal of both cultivars. The cultivar Mondial was more responsive to P fertilization and its uptake and removal of N, P, K, Ca, Mg, B, and Zn were greater than for Agata. Application rates of P2O5 exceeding 500 kg ha−1 only increased the uptake of Ca and P and the removal of P, but the plant growth and tuber yield did not increase above this P rate. The harvest index (HI) and the nutrient allocation to the tubers were not affected by the P rates and barely differed between the cultivars. Differences in nutrient removal between the cultivars were more related to the tuber DM yield than the HI.